Proyecto de Factibilidad para la Creación de una Empresa de Servicios Funerarios en el Cantón Catamayo, Provincia de Loja - Riofrio Sánchez, Adriana Alexandra (2018)
This research was carried out in the Canton Catamayo, with the purpose of offering a new company of funeral services, managing to improve the economic situation of the Canton. The main objective is to carry out a feasibility project for the creation of a funerary services company in the Canton Catamayo, Province of Loja, through this objective it will seek to implement the company determined its feasibility. For the execution of the project some methods and techniques were used that served to know the acceptance of the market, among them is the deductive and inductive method. The specific objectives are: prepare a market study, which allowed knowing the tastes, preferences and needs of consumers, knowing also the supply and demand that the funeral services company will have, it is worth mentioning that a survey was conducted at 383 families of the canton; prepare a technical study, which allowed to know the capacity that the company will have to provide the services annually, know the place of implementation, which is in the Canton Catamayo, streets Bolivar and May Day, the amount of the investment is of $ 88.406.44; Another objective is to carry out a financial study, with which it was possible to observe the income and expenses involved in carrying out said project, to prepare a financial evaluation, which served to determine the feasibility of the funeral services company through the application of the different financial indicators such as NPV, IRR, PRC, BC, giving a total Net Present Value of $ 84.801.28, therefore the project is acceptable; The Internal Rate of Return (IRR) of 18.14% being higher than the opportunity cost, therefore it is profitable, The Benefit-Cost Ratio is 0.19 dollars and the Capital Recovery Period is 3 years 4 months, with the application from each of these indicators it can be concluded that the project is totally feasible, therefore, this project can be implemented, since it has a high level of demand in the market.